METHODOLOGICAL FOUNDATIONS OF EMOTIONAL DISCOURSE ANALYSIS IN TRANSLATION STUDIES - Dinora Sodiqova (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
The methodological underpinnings of emotional speech analysis in the context of translation studies are examined in this paper. Since emotions are inherently cultural as well as linguistic, accurate translation calls for more than just exact equivalency. In order to investigate how emotional expressions are expressed and modified in English and Uzbek literary texts, the study combines descriptive-linguistic analysis, contrastive methodologies, and discourse-based approaches. In this paper, the lexical, stylistic, and pragmatic changes that take place during translation are highlighted through examples from works by Said Ahmad, Jane Austen, Abdulla Qodiriy, and William Shakespeare. The results show that cultural background and emotional intensity are important factors in preserving affective and communicative equivalency. Supported by theoretical models like Plutchik's Emotion Wheel and the writings of Kövecses and Wierzbicka, the research emphasizes the significance of incorporating semantic complexity and emotional resonance into the translation process. The article's conclusion, which has applications for both human and machine translation systems, is that a multi-layered analytical approach is necessary for translating emotional speech effectively.